ANALISA EFEKTIVITAS SISTEM INFORMASI LAPORAN LABA RUGI PADA APLIKASI MOKA DI KOPI BANG JACK HANKAM BEKASI - Tanjung Prasetyo; Arika Rahmania; Defani Gayustin (Pojok Publisher, 2024)
Every business needs to record administration to compete in strengthening its business processes. By following the development of the times, the business we run must follow the movement of the times, one of which is the use of the moka application to improve the accuracy and efficiency of business processes. This cloud data-based moka application has been widely used by business actors because the moka application provides convenience in financial administration. The purpose of this study is to find out about the effect of ease of use to compare financial reports before and after using the application, the estimation of this comparison states that the Moka application can be validated for its accuracy in recording profit and loss reports, data collection techniques using Observation Techniques, interviews and documentation studies. The results that will be obtained from this study are that caffe bang jack Hankam has implemented how to record profit and loss reports in the moka application since 2017 whose profit and loss reports are reliable and the financial data is accurate.